Investigating the barriers and success factors in implementing shariah compliant hotel operations - Zainol, Noor Azimin; Ahmad, Rozila; Mohd Shariff, Nurhazani (Medwell Journal, 2016)
Shariah compliant concept has received a special interest in various operations nowadays as people are more aware of the niche market that Islamic tourism has brought forward.However, the concept of Shariah compliance is seen as not well understood by the public, alas the implementation in the hotel operations is still mediocre.This study seeks to examine the practice of Shariah compliant concept not only by examining the barriers that mitigate the implementation of the practice but also investigating the success factors in implementing the concept in hotel operations.Qualitative stance was applied and based on the emerging themes, the barriers include “lack of awareness of Shariah compliant concept”, “negative perception of Shariah compliant operations among non-Muslims” and “operational issues of Shariah compliance concepts”.The success factors were identified as “demand and support from various sectors”,“acceptance from the guests and staff” and “instiling awareness of Shariah compliant concepts”.